Pemberian Cocopeat dan Pupuk Phonska untuk Budidaya Tanaman Ubi Jalar (Ipomoea batatas) pada Pasir Pantai Kusamba, Dawan, Klungkung - WIYANTI, WIYANTI; KUSMAWATI, TATIEK (Agrotrop : Journal on Agriculture Science, 2018)
Giving Cocopeat Compost and Phonska Fertilizer for Cultivation of Sweet Potato on Sandy Soil of Kusamba Beach, Dawan Sub District, Klungkung Regency. The purpose of the study were to know the effect of cocopeat compost and Phonska fertilizer in the physical and chemical properties, growth and production of sweet potato. The study was conducted at Green house of Agriculture Faculty Udayana University in pot experiment using the basic design of block randomized design. The treatment tested were cocopeat compost (K) at a dose of 10% (K1); 20% (K2); 30% (K3); and 40% (K4) of the weight of sand soil; and Phonska fertilizer (P) at a dose of 200 kg ha-1 (P1), and 400 kg ha-1 (P2). Each treatment was repeated 3 times. The results of the study showed that the treatment of cocopeat give the highest of total N, available P, available K, organic matter, weight of crop and tuber respectively on P4 treatment i.e. 0.06%; 414.27 ppm; 1079.59 ppm; 3.12%; 204.33 grams; and 58.74 grams, and the smallest one was in treatment of K1, i.e. 0.01%; 204.80 ppm; 577.23 ppm, 0.62%; 108.47 grams; and 11.78 grams, while the highest of Electric conductivity, pH, Bulk Density and permeability were occured by K1 amounted to 2.48 mmhos cm-1; 8,4; 1.09 grams cm-3 and 151.26 cm/hour; and the lowest was in K4 treatment i.e. 0.75 mmhos cm-1; 7.3 and 1.09 g cm-3. In the treatment of phonska the highest of total N, available P, available K, crop weight achieved by treatment of P2 i.e. 0.04%; 62.96 ppm; 788.61 ppm; 167.27 grams; and 32.35 grams, and the lowest was in the treatment of P1 i.e. 0.02%; 53.06 ppm; 709.48 ppm; 24.62 grams; and 24.62 grams.